DEVELOPING STUDENTS’ SPEAKING ABILITY THROUGH STORY COMPLETION - Hamsia, Waode (IKIP Mataram, 2018)
Speaking is a main tool of communication to others. Many people are difficult to speak English. It is caused by some factors such as need of information, less frequent of practice, low self-confidence, and so on. This research aimed to describe developing students’ speaking ability through story completion. Story Completion is very enjoyable in free-speaking activity where students sit in a circle (Kayi, 2006). There are three objectives of the research were to describe: (1) To describe the implementation of story completion in teaching speaking. (2) To describe the improvement of speaking skill for students after being given story completion. (3) To describe the students’ response to the implementation of story completion. Descriptive qualitative was applied as the method of the research while the observation was conducted to obtain the data to answer the first research about how are the implementation of story completion. The result showed that the technique of story completion was successfully implemented to improve the students’ speaking skill. The technique can make students to encourage themselves to speak up. They have to be brave and have enough self-confident when they want to talk something.